ACTIVITY OF TERMITES IN SOME SOILS OF THE COLOMBIAN ORINOQUIA - C., GALVIS; C., CHAMORRO; A., CORTÉS (Revista Colombiana de Entomología, 1978)
In the San Martín Region (Meta, Colombia) two taxonomic groups of moundconstructing termites, Coptotermes sp. and Nasutitermes sp., were studied. The mound structures average 40 centimeters in height and are constructed, by the workers, from trass materials composed of soil and digested vegetable matter. To construct the nets, the termites mainly select the clay particles, transporting, and transforming an average of 3 pounds of soil per square meter; this alters the structural profile of the soils. The water carrying capacity, pH, organic matter, the capacity of ionic exchanges, available phosphorus, and the overall composition of the nest site is better than the those found in the surrounding soil. Soil density and porosity are also significantly altered. Soil humidity is the main factor determining termite nest location. The nested pattern is distinctively clumped in the low, poorly drained areas. The presence of subterranean termites can be considered beneficial to the microenvironment of the soil as a result of the modifications introduced in the soil-plant relationship.